Bone phenotypes in multiple endocrine neoplasia type 1: survey on the MEN1 Florentine database. Issue 5 (11th May 2022) - Marini, Francesca; Giusti, Francesca; Iantomasi, Teresa; Cioppi, Federica; Brandi, Maria Luisa
Abstract : Multiple endocrine neoplasia type 1 (MEN1) is a rare, inherited cancer syndrome characterized by the development of multiple endocrine and non-endocrine tumors. MEN1 patients show a reduction of bone mass and a higher prevalence of early onset osteoporosis, compared to healthy population of the same age, gender, and ethnicity. During the monitoring and follow-up of MEN1 patients, the attention of clinicians is primarily focused on the diagnosis and therapy of tumors, while the assessment of bone health and mineral metabolism is, in many cases, marginally considered. In this study, we retrospectively analyzed bone and mineral metabolism features in a series of MEN1 patients from the MEN1 Florentine database. Biochemical markers of bone and mineral metabolism and densitometric parameters of bone mass were retrieved from the database and were analyzed based on age ranges and genders of patients and presence/absence of the three main MEN1-related endocrine tumor types. Our evaluation confirmed that patients with a MEN1 diagnosis have a high prevalence of earlyonset osteopenia and osteoporosis, in association with levels of serum and urinary markers of bone turnover higher than the normal reference values, regardless of their different MEN1 tumors. Fifty percent of patients younger than 26 years manifested osteopenia and 8.3% had osteoporosis, in at least one of the measured bone sites. These data suggest the importance of including biochemical and instrumental monitoring of bone metabolism and bone mass in the routine medical evaluation and follow-up of MEN1 patients and MEN1 carriers as important clinical aspects in the management of the syndrome.